A low‐profile dual‐band omnidirectional Alford antenna for wearable WBAN applications. Issue 5 (24th January 2020) - Wang, Wei; Xuan, Xiu‐Wei; Pan, Peng; Hua, Yu‐Jie; Zhao, Hai‐Bo; Li, Kun
Abstract: A low‐profile omnidirectional antenna based on folded Alford loop is proposed for wireless body area network (WBAN) applications in industrial, scientific, and medical (ISM, 2.4‐2.4835 GHz and 5.725‐5.875 GHz) bands. By fabricating two complementary symmetrically folded Alford loops on both sides of a round Roger substrate, the proposed antenna has small volume and omnidirectional radiation capability in both bands. Since the omnidirectional radiation plane is parallel to the human body surface, low specific absorption rate (SAR) can be obtained. The proposed antenna has a profile of 0.639 mm and occupies an area of π  × 30 2  mm 2, along with a measured peak gain of 6.1 dBi and 14.1% impedance bandwidth (BW) at 2.45 GHz and peak gain of 2.2 dBi and 6.7% impedance BW at 5.8 GHz. Simulated and measured results reveal that the antenna has good omnidirectional radiation in both bands. Moreover, the bending sensitivity study and SAR analysis prove that it is a good candidate for wearable WBAN devices.